2019
DOI: 10.1371/journal.pone.0211316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stone-free rates following shock wave lithotripsy, percutaneous nephrolithotomy, and retrograde intrarenal surgery for treatment of renal stones: A systematic review and network meta-analysis

Abstract: Objectives To perform a systematic review and network meta-analysis comparing stone-free rates following retrograde intrarenal surgery (RIRS), extracorporeal shock wave lithotripsy (SWL), and percutaneous nephrolithotomy (PCNL) treatments of renal stones. Materials and methods Clinical trials comparing RIRS, SWL, and PCNL for treatment of renal stones were identified from electronic databases. Stone-free rates for the procedures were compared by qualitative and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 82 publications
3
46
0
6
Order By: Relevance
“…The treatment options for stone disease range from open surgery to endoscopic surgery, such as percutaneous nephrolithotomy (PCNL) and ureteroscopy (URS) (Heinze, Gozen & Rassweiler, 2019). Generally, PCNL results in higher stone-free rate than URS, at the expense of elevated complication rate and prolonged hospital stays, without difference in secondary interventions (De et al, 2015;Chung et al, 2019). However, infection remains a main complication that can cause longer length of stay and even lethal sepsis shock (Kreydin & Eisner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment options for stone disease range from open surgery to endoscopic surgery, such as percutaneous nephrolithotomy (PCNL) and ureteroscopy (URS) (Heinze, Gozen & Rassweiler, 2019). Generally, PCNL results in higher stone-free rate than URS, at the expense of elevated complication rate and prolonged hospital stays, without difference in secondary interventions (De et al, 2015;Chung et al, 2019). However, infection remains a main complication that can cause longer length of stay and even lethal sepsis shock (Kreydin & Eisner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additional medical management with selective alpha‐receptor antagonists in stones less than 10 mm diameter has demonstrated efficacy for promoting stone passage 4 . Despite these measures, 10–20% of urolithiasis will require surgical management with extracorporeal shock‐wave lithotripsy (ESWL), retrograde intrarenal surgery with ureteroscopy and laser lithotripsy or percutaneous nephrolithotomy (PCNL) 5 . Whilst ESWL is less invasive, laser lithotripsy can perform stone dusting and fragmentation under direct endoscopic vision; and has the added advantage of directly removing fragmented stones using a basket for stone analysis.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to PCNL, the SFR after ESWL and RIRS is getting increasingly concerned, since spontaneous passage of stone fragments following ESWL and RIRS is more required than PCNL. It has been reported that SFR ranges from 23.1 to 91.5% and 45.6 to 96.7% in ESWL and RIRS, respectively [12]. Residual stone fragments related complications are foreseeable, urinary tract infection, renal colic and steinstrasse are most common and might require additional intervention [13,14].…”
Section: Introductionmentioning
confidence: 99%